A program for optical observations of advanced LIGO early triggers in the southern hemisphere. Issue 67 (17th July 2015) - Benacquista, M.; Belczynski, C.; Beroiz, M.; Branchesi, M.; Colazo, C.; Diaz, M.C.; Dominguez, M.; Garcia Lambas, D.; Liang, S.; Macri, L.; Peñuela, T.; Sanchez, B.; et al.
Abstract : In this poster we present a plan to follow-up optically early triggers from the Advanced LIGO gravitational wave detectors, which will start operating in scientific mode in the northern summer of 2015.